2019
DOI: 10.1038/s41418-019-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 is required for the regionalization of retrosplenial cortex

Abstract: The retrosplenial cortex (Rsp) is a transitional cortex located between the neocortex and archicortex, but the molecular mechanism specifying Rsp from the archicortex remains elusive. We here report that the transcription factor Satb2 is required for specifying Rsp identity during its morphogenesis. In Satb2 CKO mice, the boundary between the Rsp and archicortex [i.e., subiculum (SubC)] disappears as early as E17.5, and Rsp efferent projection is aberrant. Rsp-specific genes are lost, whereas SubC-specific gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The function of Nurr1 and its role in development of dopaminergic neurons has been studied in detail ( Zetterström et al, 1997 ; Sakurada et al, 1999 ; Hermanson et al, 2003 ; Eells et al, 2006 ). Interestingly, a recent study has found that in the medial pallium Nurr1 is repressed by Satb2 and promotes subiculum identity in the absence of Satb2 ( Zhang et al, 2020 ). However, so far little is known about the role of Nurr1 expression in claustrum development.…”
Section: Discussionmentioning
confidence: 99%
“…The function of Nurr1 and its role in development of dopaminergic neurons has been studied in detail ( Zetterström et al, 1997 ; Sakurada et al, 1999 ; Hermanson et al, 2003 ; Eells et al, 2006 ). Interestingly, a recent study has found that in the medial pallium Nurr1 is repressed by Satb2 and promotes subiculum identity in the absence of Satb2 ( Zhang et al, 2020 ). However, so far little is known about the role of Nurr1 expression in claustrum development.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if regions exhibiting enrichment in H3k9me2 also display increased occupancy of SATB2 , we conducted ChIP-qPCR analysis using the previously validated antibody [ 53 55 ]. As a positive control, we assayed the enrichment of H3K9me2 and SATB2 at the SOX5 binding site within enhancer 434, upstream of the gene encoding Fezf2 [ 53 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Satb2 has been implicated in cell type-specific activities during mouse neural development and has the potential to act both as an activator and a repressor 20 , 23 , 24 , 41 . To better understand the function of Satb2 during differential cell fate specification, we performed single-cell RNA-seq analysis on wild-type siblings ( satb2 +/+ ) and mutants ( satb2 −/− ) at 14 ss (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%